Enhancement of Properties of Coir Geotextiles by Natural Rubber Latex Coating - Nair, Lekshmi; Ravi, P. K.; Sarma, U. S. (International Coconut Community, 2011)
Coir geotextiles find application in revegetation of slopes by stabilizing the soil through erosion control. It has been found that the longevity of coir geotextiles although highest among all the natural fibres, it is required to last for at least 5 years so as to sustain the vegetation on the slopes for a long term solution. Normally it is found that coir geotextiles lose their 50% strength in 6 months in contact with soil, therefore it is required to strengthen the coir geotextiles. This work involves the coating of coir geotextiles with natural rubber latex which could enhance the longevity of coir geotextiles in various civil/bio engineering applications. The rubber latex coated coir geotextiles which are eco-friendly have superior mechanical properties and better durability compared to the conventional uncoated coir geotextiles. This paper reports the coating of coir geotextile using natural rubber latex and a comparative study of the physical and mechanical properties of the treated and untreated coir geotextiles.